Long-COVID: Current Understanding and Future Directions - Shukla, Deepak (International Journal of Medical Research, 2025)
Long-COVID, or post-acute sequelae of SARS-CoV-2 infection, represents a significant global health challenge characterized by persistent symptoms lasting months after acute COVID-19. This narrative review synthesizes current understanding, exploring epidemiology, pathophysiology, clinical manifestations, diagnosis, management, and future directions. Prevalence estimates suggest 10-30% of survivors experience Long-COVID, with higher rates in women, middle-aged adults, and those with severe initial infections. Proposed mechanisms include viral persistence, immune dysregulation, endothelial dysfunction, and multi-organ damage, though causality remains uncertain due to observational study limitations. Common symptoms-fatigue, dyspnea, cognitive impairment, and joint pain-span systemic, respiratory, cardiovascular, and neurological domains, severely impacting quality of life. Diagnosis relies on clinical history and exclusion of differentials, lacking specific biomarkers. Management is symptom-focused, involving multidisciplinary rehabilitation, pacing, and emerging pharmacological trials, though evidence is limited by small sample sizes and biases. Future research prioritizes standardized definitions, longitudinal studies, and biomarker discovery to enable targeted therapies. Public health strategies must address inequities and integrate surveillance. Despite advances, gaps in understanding prognosis and treatment persist, necessitating increased funding and interdisciplinary collaboration to mitigate Long-COVID’s long-term burden and inform pandemic preparedness.